1997
DOI: 10.1002/marc.1997.030180604
|View full text |Cite
|
Sign up to set email alerts
|

Lipase‐catalyzed ring‐opening polymerization of lactide

Abstract: The six-membered lactide was polymerized using the ring-opening polymerization with lipase as a catalyst at a temperature between 80 and 130°C in bulk to yield the corresponding polylactide with weight-average molecular weights of up to 126000. The most preferable conditions with respect to the molecular weight of the polylactide are the bulk polymerization using lipase PS at a temperature of 100°C. The D,L-lactide gave higher molecular weight compared to the D,D-and L,L-lactide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(68 citation statements)
references
References 23 publications
3
63
0
1
Order By: Relevance
“…Conversion of lactide to the oligo-and polylactides was determined by comparison of the 1 H NMR spectral integration intensities of the peaks at = 5.0 ppm corresponding to the methine group of the monomeric lactide with the methine proton of the oligo-and polylactides at = 5.2ppm [9,11].…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversion of lactide to the oligo-and polylactides was determined by comparison of the 1 H NMR spectral integration intensities of the peaks at = 5.0 ppm corresponding to the methine group of the monomeric lactide with the methine proton of the oligo-and polylactides at = 5.2ppm [9,11].…”
Section: Instrumentsmentioning
confidence: 99%
“…By the first report on the lipase catalyzed ring-opening polymerization of lactides by Matsumura, et al. [9], some lipases were used to polymerize In this paper, we are going to report a novel synthesis method to develop the poly(L,L-lactide) by enzymatic ring-opening polymerization by using immobilized lipase CA as a catalyst under a new and the most simple reaction condition from L,L-lactide (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, enzymes represent a family of "environmentally friendly" catalysts, because enzymatically polymerized polyesters are potentially biodegradable. Recently, the enzymatic synthesis of lactide has been studied 23) . Polylactide is a biodegradable and bioabsorbable material.…”
Section: Introductionmentioning
confidence: 99%
“…To that end, the current microbial cell factory ought to be improved with further evolved LA-polymerizing enzymes (LPE) and metabolic engineering-based optimization (Taguchi, 2010). Matsumura et al (Matsumura et al, 1997) likewise reported the lipase PC-catalyzed polymerization of cyclic diester-D,L-lactide at a temperature of 80-130°C to yield poly(lactic acid) with molecular masses of up to 12,600. Other novel methods (e.g.…”
Section: New Approachesmentioning
confidence: 99%